Factors Affecting the Development of Information Technology in the World of Education - Sinta Ulina Situmorang; Oktavianus (Jurnal Pendidikan Vokasi Indonesia, 2022)
Education is an effort and through stages or processes to educate and develop the potential from within humans, provide broad insight, have creativity, be responsible, and education to make ideas or patterns of human thinking better and more useful. The development of science and technology is in line with human development. These developments cause significant changes for humans, especially in the field of education which has both positive and negative sides. There are 2 ways that educators can do to attract students' interest in learning by using the internet and minimizing the use of the internet which makes students put aside their duties or responsibilities as a student, namely using the internet as a learning medium. use the internet according to educational needs. In addition, the use of the internet as a learning medium greatly facilitates students in accessing knowledge information, sending school assignments via email, and so on, and besides that, another way that can attract students' interest in learning is through learning methods. As educators, teachers are required to sort out suitable and appropriate learning models to deliver a concept to their students. To achieve maximum learning outcomes, an effort that a teacher can try is to use a suitable learning model in delivering learning to students.